Strategi Guru Dalam Mengembangkan Kreativitas Anak Usia Dini Melalui Kegiatan Seni Melipat Kertas - Luthffiah, Alya; Lestari, Fadilla; Nursyahada, Hanifah (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This article discusses teacher strategies in developing early childhood creativity through paper folding (origami) art activities as a response to the challenges of 21st-century education that demand a creative and holistic learning approach. The urgency of this study lies in the need to revitalize manual activities amidst the dominance of digital technology that has an impact on the decline in children’s motor and imaginative skills. This study uses a qualitative method with a literature study approach, reviewing academic literature sources to build a learning strategy model based on the exploration process. The results of the analysis show that effective strategies involve flexible, step-by-step instructions, free exploration space, creative reflection, and the role of teachers as facilitators. These findings are reinforced by the theory of constructivism (Piaget Vygotsky) which emphasizes active and social learning, and the theory of multiple intelligences (Gardner) which emphasizes the importance of developing various domains of children’s potential. Origami has been shown to support the development of fine motor skills, spatial cognition, flexibility of thinking, and children’s adaptive character. In conclusion, the art of paper folding can be optimized as a strategic pedagogical instrument in building creativity and learning readiness in early childhood in a comprehensive and sustainable manner.